ECOTOURISM DEVELOPMENT STRATEGY OF TANGGAMUS REGENCY, LAMPUNG PROVINCE (CASE STUDY: TELUK KILUAN) - Fariz Fardani Nurbaihaqi; Enok Maryani; Rini Andari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This research was conducted to identify the potential of ecotourism in Tanggamus district in optimizing the role of tourism in the economy and community welfare, it is necessary to develop a sustainable tourism development based on an adequate understanding of the characteristics, conditions and constraints faced by tourism business actors. This development needs to be supported by appropriate financing and investment schemes. This research is qualitative research with a descriptive method with an inductive approach or solving existing problems and finding a complete understanding of the object being observed with research, as well as collecting data through direct observations made by researchers on 25-28 February 2022, interviews and documentation. In collecting qualitative data, the author conducted interviews with 20 informants using the snowball method consisting of the Head of the Tourism and Culture in Tanggamus Regency, Communities around tourist objects, tourists, managers, and MSME business actors. The development of tourist areas has not involved stakeholders outside the village, such as universities and the private sector. The absence of regulations on the management of ecotourism areas, the lack of budget allocations, the absence of a uniform cost system related to entrance tickets and profit sharing between the village and the manager, the opportunistic behavior of a small part of the community are institutional obstacles in the development of the ecotourism area. Based on the results of the study in this study, the proposed development of coastal ecotourism areas is sustainable tourism, which involves local governments, the private sector, academics, local communities, and the mass media.